A versatile high-performance LC-MS/MS assay for the quantification of voriconazole and its N-oxide metabolite in small sample volumes of multiple human matrices for biomedical applications - Schulz, Josefine; Michelet, Robin; Joseph, Jan Felix; Zeitlinger, Markus; Schumacher, Fabian; Mikus, Gerd; Kloft, Charlotte (Journal of pharmaceutical and biomedical analysis, 2022)
Voriconazole (VRC) pharmacokinetics, in particular its complex metabolism, is still not fully understood which challenges its optimal therapeutic use. To increase knowledge on the pharmacokinetics of this antifungal drug, it is essential to broaden the perspective and expand in vitro and clinical in vivo investigations in particular to aspects such as unbound plasma, target-site and metabolite concentrations. Innovative sampling approaches such as microdialysis, a minimally-invasive technique for the analysis of compound concentrations in target-site human tissue fluids, are associated with bioanalytical challenges, i.e. small sample volumes and low concentrations. Thus, a bioanalytical LC-MS/MS assay for the simultaneous quantification of VRC and its main N-oxide (NO) metabolite in human plasma, ultrafiltrate and microdialysate was developed and validated according to the European Medicines Agency guideline. Quantification was rapid, simple and feasible for clinically relevant concentrations from 5 to 5000 ng/mL in plasma and ultrafiltrate as well as from 4 to 4000 ng/mL in microdialysate. Due to the high sensitivity of the assay, only 20 µL of plasma or ultrafiltrate and 5 µL of microdialysate were required. For VRC and NO in all matrices, between-run accuracy was high with a maximum mean deviation of 7.0% from the nominal value and between-run precision was demonstrated by ≤ 11.8% coefficient of variation. Both compounds proved stable under various conditions. The assay suitability was demonstrated by the application to a clinical study quantifying simultaneously VRC and NO concentrations in plasma, ultrafiltrate and microdialysate. Additionally, the assay was successfully adapted for pharmacokinetic analyses in human tissue-derived in vitro experiments. Overall, by reducing the required sample volume, the bioanalytical method allows for an increased number of plasma samples in vulnerable populations, e.g. infants, and enables the generation of concentration-time profiles with a higher temporal resolution in microdialysis studies. Consequently, the developed assay is apt to elucidate the complex pharmacokinetics of VRC in clinical settings as prerequisite for therapy optimisation.